Perspekif Guru Terhadap Pembelajaran yang Efektif dalam Pembelajaran IPAS di Sekolah Dasar - ramadani, Putri (LP2M STAI Darul Kamal NW Kembang Kerang, 2024)
The purpose of this study was to analyze the teacher's perspective on effective learning in science and social sciences (science and social sciences) in elementary schools. The researcher felt the need to conduct further research on the perceptions of elementary school teachers towards effective learning in science and social sciences subjects contained in the Independent Curriculum. The research method used was a qualitative descriptive method. The results of the study showed that elementary school teachers gave a positive response to the science and social sciences subjects contained in the Independent Curriculum. Effective science and social sciences learning is considered to have a positive impact because it can reduce the burden on teachers in pursuing material so that teachers have plenty of time to explore various models and learning methods that are interesting for students. The results of the study also showed that teachers were considered ready to implement science and social sciences learning in elementary schools, as evidenced by the planning, implementation and assessment that had been prepared carefully.